Proceso atención de enfermería a paciente joven de 20 años con traumatismo craneoencefálico. - Salinas Landy, Luis Gabriel (2021)
This work compiles the clinical case of a patient with head trauma due to a fall at home, this case was presented at the Liborio Panchana General Hospital, in the emergency department. For this case, the diagnostic methodology was implemented which investigates the clinical history of the patient, the formulation of presumptive, differential and definitive data, as well as their respective follow-up and reviews. Head trauma is any type of trauma to the scalp, skull, and brain. Injuries can be from a small area or bulge in the skull, contusion, wound on the scalp. In the theoretical framework, all relevant information from various authors and medical journals on the case presented here and its procedures for treatment and subsequent review is also emphasized. The present case is one of the most common emergencies. The same as according to the national institute of statistics and censuses INEC, hospital admissions for trauma only in the province of Santa Elena there are 20,745 cases of the male sex and 10,006 of the female sex. This trauma can cause bleeding in the brain internal tissue, as well as subarachnoid hemorrhages, subdural and extradural hematomas. In addition to symptoms such as loss of consciousness, vision, headaches, changes in behavior, confusion or amnesia and in rare cases loss of the sense of taste. And in the most serious cases, seizures or seizures, inability to move, loss of coordination, vomiting, difficulty speaking may occur, in these cases it is necessary to attend to the patient in a timely manner.